2015
DOI: 10.4049/jimmunol.1403207
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Leucine Zipper: A Critical Factor in Macrophage Endotoxin Tolerance

Abstract: Induction of glucocorticoid-induced leucine zipper (GILZ) by glucocorticoids plays a key role in their anti-inflammatory action. In activated macrophages, GILZ levels are downregulated via tristetraprolin-mediated GILZ mRNA destabilization. To assess the functional significance of GILZ downregulation, we generated myeloid-specific GILZ knockout (KO) mice. GILZ-deficient macrophages displayed a higher responsiveness toward LPS, as indicated by increased TNF-α and IL-1β expression. This effect was due to an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(98 citation statements)
references
References 50 publications
6
92
0
Order By: Relevance
“…We found that both in vitro and in vivo GILZ expression was enhanced as early as 3 h after GC (DEX) treatment. Upregulation of GILZ by DEX was previously also reported in circulating neutrophils in humans and correlated with apoptosis (16); thus, it seems that neutrophils are another myeloid cell type in which GILZ plays an important role (15,30,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that both in vitro and in vivo GILZ expression was enhanced as early as 3 h after GC (DEX) treatment. Upregulation of GILZ by DEX was previously also reported in circulating neutrophils in humans and correlated with apoptosis (16); thus, it seems that neutrophils are another myeloid cell type in which GILZ plays an important role (15,30,35).…”
Section: Discussionmentioning
confidence: 99%
“…In cells of the innate immune system, GILZ, like GCs, prevents dendritic cells from activating antigen-specific T lymphocytes, and in macrophages, down-regulation of GILZ induces a proinflammatory response (14,15). There is little information on the function of GILZ in neutrophils, and only one recent work has demonstrated that GILZ is important for neutrophil apoptosis in humans (16).…”
mentioning
confidence: 99%
“…Importantly, we found TSC22D3, also known as GILZ, among the genes which were specifically upregulated in IL-10-APC. This transcription factor is described to be a critical factor in macrophage endotoxin tolerance 13 and could explain the absent response of IL-10-APC to LPS. The immunoregulatory actions of TSC22D3 are considered to be mediated, in part, via the inhibition of NF-kB and AP-1.…”
Section: Il-10-apc Display Relevant Cell Intrinsic Differences Comparmentioning
confidence: 99%
“…Loss of GILZ has also been shown to enhance extracellularsignal regulated kinase (ERK) signaling in murine bone marrow-derived macrophages (20). Therefore, we examined LPSinduced ERK activation in curcumin-treated WT and GILZ KO BMMs.…”
Section: Resultsmentioning
confidence: 97%
“…6, C-F). Both ERK and NF-B are involved in LPS-induced TNF-␣ production in murine BMMs (20). Thus, we also examined the inhibitory effects of curcumin on TNF-␣ secretion in WT and GILZ KO cells.…”
Section: Resultsmentioning
confidence: 99%